La infraestructura en base a los estándares de calidad en educación y su relación con la seguridad de los niños y niñas de 5 – 6 años de las escuelas “Chile”, “Portoviejo” y “Luz de América” del cantón Calvas. Lineamientos propositivos - Erazo Rodríguez, Marta (2014)
This thesis refers to: INFRASTRUCTURE BASED ON QUALITY STANDARDS IN EDUCATION AND ITS RELATIONSHIP WITH THE SAFETY OF CHILDREN 5-6 YEARS OF SCHOOLS "CHILE", "PORTOVIEJO" Y "LIGHT OF AMERICA" CANTON AND BALD. GUIDELINES proactive. Being structured and developed according to the Rules of Effective Undergraduate National University of Loja same. The general objective that was raised was: Analyze the content of the field of infrastructure of schools, "Chile", "Portoviejo" and "Light of America" quality standards in education and its impact on the safety of children aged 5 - 6 years. The use of methods for the preparation of this research work were: Scientist, Analytical and Descriptive, Synthetic, Inductive, Deductive and Statistical Model, including techniques and tools applied to teachers surveys for quality standards in education and its impact on the safety of children in schools, "Chile", "Portoviejo" and "Light of America"; and children a Guide observation applied to see what level of security have in school was used. The threats that may affect infrastructure are earthquakes with 67%, vulnerabilities classroom represent 10% who are furniture are detached from the wall, the building presents a vulnerability of 20% at the conditions of your roof, and in regard to the outer space by 10% have green spaces. You need 67% in education incorporate the issue of child safety in schools, 25% believe it is important to prevent childhood accidents, 15% know that security and 10% do not know when a risk is in the institution